New Zealand Consumer Interest Growing for 5G Mobile - Pugh, Nigel (Journal of Telecommunications and the Digital Economy, 2019)
This paper summarizes results from a survey of the New Zealand mobile market by Venture Insights in October 2018. The survey had over 1,000 respondents, all of whom were responsible for making their mobile purchasing decisions, with a representative spread across New Zealand, all adult age groups, and customers from the three major mobile service providers. The survey identified a strong consumer interest in and awareness of 5G, with 31% of respondents willing to consider a move to 5G within two years of launch. Mobile video will be a strong driver, with 69% of respondents having viewed video on their mobile and, again, a willingness to move to 5G within two years. Fixed wireless broadband service was also strongly supported, with 18% of those with a household fixed broadband service indicating a possible transition within two years to a 5G fixed wireless service. However, the Ultra-Fast Broadband fixed service is likely to be a strong competitor to fixed wireless broadband.